Gene Cloning, Purification, and Characterization of a Cold-Active Alkaline Lipase from Bacillus cereus U2 - Baoxiang He; Ning Li; Yan Qin; Liang Xian; Jin Zhou; Sijia Liu; Jing Zhang; Jingtao Wu; Qingyan Wang; Xinquan Liang (Fermentation, 2025)
Lipases are important industrial enzymes with a wide range of applications across various sectors. Cold-active lipases are particularly well suited for industrial processes that operate at low temperatures (such as food processing and environmental remediation) due to their high catalytic efficiency and energy-saving benefits. In this study, a novel lipase—LipU (GenBank accession: PV094892)—was heterologously expressed from Bacillus cereus U2 and characterized for its low-temperature adaptability and alkaline resistance. LipU belongs to the lipase Subfamily I.5 and shares the highest amino acid sequence identity (53.32%) with known homologs. Enzymatic assays revealed that LipU exhibits optimal activity at 20 °C and pH 11. It retained 95% of its initial activity after 24 h of incubation at 4 °C and pH 11.0. Furthermore, the activity of LipU was enhanced by Ca2⁺, Na⁺, Tween 20, and Tween 80, whereas it was inhibited by Cu2⁺, Zn2⁺, Mn2⁺, and sodium dodecyl sulfate (SDS). LipU demonstrated tolerance to various organic solvents of differing polarity; after 1 h of exposure to 15% (v/v) ethanol, n-butanol, isoamyl alcohol, dimethyl sulfoxide, or glycerol, it retained over 78.6% of its activity. These properties make LipU a promising candidate for industrial applications, including for leather degreasing, alkaline wastewater treatment, and low-temperature biocatalysis.